ADHD and Psychiatric Comorbidity: Functional Outcomes in a School-Based Sample of Children. Issue 9 (July 2020) - Cuffe, Steven P.; Visser, Susanna N.; Holbrook, Joseph R.; Danielson, Melissa L.; Geryk, Lorie L.; Wolraich, Mark L.; McKeown, Robert E.
Objective: Investigate the prevalence and impact of psychiatric comorbidities in community-based samples of schoolchildren with/without ADHD.Method: Teachers and parents screened children in South Carolina (SC; n = 4, 604) and Oklahoma (OK; n = 12, 626) for ADHD. Parents of high-screen and selected low-screen children received diagnostic interviews (SC: n = 479; OK: n = 577).Results: Psychiatric disorders were increased among children with ADHD and were associated with low academic performance. Conduct disorder/oppositional defiant disorder (CD/ODD) were associated with grade retention (ODD/CD + ADHD: odds ratio [OR] = 3.0; confidence interval [CI] = [1.5, 5.9]; ODD/CD without ADHD: OR = 4.0; CI = [1.7, 9.7]). School discipline/police involvement was associated with ADHD alone (OR = 3.2; CI = [1.5, 6.8]), ADHD + CD/ODD (OR = 14.1, CI = [7.3, 27.1]), ADHD + anxiety/depression (OR = 4.8, CI = [1.6, 14.8]), and CD/ODD alone (OR = 2.8, CI = [1.2, 6.4]). Children with ADHD + anxiety/depression had tenfold risk for poor academic performance (OR = 10.8; CI = [2.4, 49.1]) compared to children with ADHD alone. This should be interpreted with caution due to the wide confidence interval.Conclusion: Most children with ADHD have psychiatric comorbidities, which worsens functional outcomes. The pattern of outcomes varies by type of comorbidity.